A randomized, placebo-controlled trial of canakinumab in patients with peripheral artery disease. (October 2019) - Russell, Kerry S; Yates, Denise P; Kramer, Christopher M; Feller, Andrea; Mahling, Ping; Colin, Laurence; Clough, Timothy; Wang, Tianke; LaPerna, Lucy; Patel, Alpa; Lawall, Holger; Shennak, Mustafa M; et al.
Extensive atherosclerotic plaque burden in the lower extremities often leads to symptomatic peripheral artery disease (PAD) including impaired walking performance and claudication. Interleukin-1β (IL-1β) may play an important pro-inflammatory role in the pathogenesis of this disease. Interruption of IL-1β signaling was hypothesized to decrease plaque progression in the leg macrovasculature and improve the mobility of patients with PAD with intermittent claudication. Thirty-eight patients (mean age 65 years; 71% male) with symptomatic PAD (confirmed by ankle–brachial index) were randomized 1:1 to receive canakinumab (150 mg subcutaneously) or placebo monthly for up to 12 months. The mean vessel wall area (by 3.0 T black-blood magnetic resonance imaging (MRI)) of the superficial femoral artery (SFA) was used to measure plaque volume. Mobility was assessed using the 6-minute walk test. Canakinumab was safe and well tolerated. Markers of systemic inflammation (interleukin-6 and high-sensitivity C-reactive protein) fell as early as 1 month after treatment. MRI (32 patients at 3 months; 21 patients at 12 months) showed no evidence of plaque progression in the SFA in either placebo-treated or canakinumab-treated patients. Although an exploratory endpoint, placebo-adjusted maximum and pain-free walking distance (58 m) improved as early as 3 months after treatment with canakinumab when compared with placebo. Although canakinumab did not alter plaque progression in the SFA, there is an early signal that it may improve maximum and pain-free walking distance in patients with symptomatic PAD. Larger studies aimed at this endpoint will be required to definitively demonstrate this.ClinicalTrials.gov Identifier: NCT01731990